Tingkat Keaktifan Anak Tunagrahita dalam Pembelajaran Pendidikan Jasmani di SMPLB C Tunas Harapan Karawang - Mohammad Arif; Ruslan Abdul Gani; Aria Kusuma Yuda (Jurnal Speed (Sport, Physical Education, Empowerment), 2022)
Research is a research qualitative . The method that is used is a survey with tekink retrieval of data using interview guide and checklist. The subjects in this study were seventh, eighth and ninth grade students at C Tunas Harapan Karawang High School. The population is all students at C Tunas Harapan Karawang High School, totaling 25 Respondents. The sample used is 9 children taken from each class, 3 children. The research data was collected directly through: 1) observation guidelines, 2) interview guides, 3) documentation. Analysis of the data in this study is a descriptive analysis as outlined in the form of a percentage.